EP.TH.803VAE for Breast Lesions of Uncertain Potential (B3) -A Quality Improvement Project. (28th October 2021) - Sandhya, Anu; Dent, Helen; Oyewole, Bankole; Pogson, Caroline; Silva, Tania De; Waheed, Shamaela; Perera, Iroshini
Abstract: Aims: Breast lesions of uncertain malignant potential (B3) account for 7% breast lesions biopsied. Management has been controversial and challenging for the MDT. Aim of the study was to compare current NHS BSP guidelines with our trust's practice and the secondary outcome was a shorter patient pathway and cost effectiveness. Methods: As per NHS BSP guidelines VAE should be performed for all B3 lesions diagnosed on 14g or vacuum assisted biopsy. We were referring them to other NHS trusts as there were no in-house facilities or doing an excisional biopsy if no resources for VAE available. From September 2019 VAEs started to be done by in-house consultant breast radiologist after getting the appropriate training and instruments. Data was collected from September 2019 to August 2020 for all patients. Results: 22 VAEs were performed in one year. Out of those 6 (27.2%) were upgraded to malignancy and needed further surgery, 2 (9%) with atypia had 5 years mammographic surveillance and 14 (63%) were discharged including sclerosing lesions, radial scars, fibrosis and chronic inflammation. The cost of VAE in our hospital is £1330 vs. £2439 for Wire Guided wide local excision. This makes it cost effective. Conclusion: We were following the VAE protocol as per NHS BSP guidelines. Despite added workload to radiology VAE is minimally invasive, safe and cost effective alternative to surgery providing thorough MDT discussion has taken place. Greater benefit was provided to patient as all VAEs were performed in radiology department avoiding general Anaesthesia and surgical trauma.